Knowledge Structure and Emerging Trends of Telerehabilitation in Recent 20 Years: A Bibliometric Analysis via CiteSpace - Zheng, Jiaqi; Hou, Meijin; Liu, Lu; Wang, Xiangbin (Frontiers in Public Health, 2022)
Purpose Telerehabilitation, as an effective means of treatment, is not inferior to traditional rehabilitation, and solves the problem of many patients who do not have access to hospital-based training due to costs and distance. So far, the knowledge structure of the global use of telerehabilitation has not been formed. This study aimed to demonstrate the state of emerging trends and frontiers concerning the studies of telerehabilitation through bibliometric software. Methods Literature about telerehabilitation from 2000 to 2021 was retrieved from the Web of Science Core Collection. We used CiteSpace 5.8.R3 to analyze the publication years, journals/cited journals, countries, institutions, authors/cited authors, references, and keywords. Based on the analysis results, we plotted the co-citation map to more intuitively observe the research hotspots and knowledge structure. Results A total of 1,986 records were obtained. The number of annual publications gradually increased over the investigated period. The largest increase occurred between 2019 and 2020. J TELEMED TELECARE was the most prolific and the most cited journal. The United States was the most influential country, with the highest number of publications and centrality. The University of Queensland was the most productive institution. The author Tousignant M ranked the highest in the number of publications and Russell TG ranked the first in the cited authors. Respectively, the articles published by Cottrell MA and Russell TG ranked the first in the frequency and centrality of cited references. The four hot topics in telerehabilitation were “care”,“stroke”, “telemedicine” and “exercise”. The keyword “stroke” showed the strongest citation burst. The two frontier keywords were “physical therapy” and “participation”. The keywords were clustered to form 21 labels. Conclusion This study uses visualization software CiteSpace to provide the current status and trends in clinical research of telerehabilitation over the past 20 years, which may help researchers identify new perspectives concerning potential collaborators and cooperative institutions, hot topics, and research frontiers in the research field. Bibliometric analysis of telerehabilitation supplements and improves the knowledge field of telemedicine from the concept of rehabilitation medicine and provides new insights into therapists during the COVID-19 pandemic.